Nutrition education services in hospitals and the nutrition knowledge of patients - Natividad, Eileen S. C. Reyes
This study examined the nature and extent of nutrition education services delivered to the patient by the medical team, and the nutrition knowledge of patients. Data were obtained through the use of a questionnaire from 1861 individuals in 86 hospitals in Luzon and Visayas. The respondents were composed of 220 doctors, 431 nurses, 70 persons-in-charge of the dietary service (PIC), of whom 40 percent were non-nutritionists/ dietitians (N/D), and 960 patients. Variations existed in the delivery of nutrition education services by the doctors, nurses, and PICs to hospital patients. These three groups differed in terms of the following: 1. kinds of patient to whom diet instruction was given, 2. time and length of instruction, 3. inquiries made on the patient's food intake, 4. kinds of information given to the patient, and 5. the number of days a patient is placed on a diet. The factors that were found to be significantly related to the nutrition education practices of the medical team, either during the initial meeting with the patient or during his stay in the hospital, were the hospital's bed size, availability of a N/D in the hospital, specialties of doctors, and the kinds of nurses. The nutrition education services which the patients said they received were consistemtn with the report of the doctors, nurses, and PICs. Vitamin was the nutrient most heard of or known by the patines, while calories was the "nutrient" least heard of or known. About one of the two patients claimed he heard about the nutrition claims listed, however only one our of the three claimed they knew the meaning, function and sources of the nutrients listed. Furthermore, of the various sociodemographic factors studied, only educational attainment was found significantly related to the mean test scores of the patients.